Spatial variation in lag structure in the short-term effects of air pollution on mortality in seven major South Korean cities, 2006–2013. (April 2019) - Kim, Honghyok; Kim, Hyomi; Lee, Jong-Tae
Abstract: Lag is one of the major uncertainties in the heterogeneity of short-term effects of particulate matter with aerodynamic diameter <10 μm (PM10 ) on mortality. This study aimed to explore spatial variations in extended lag effects of PM10 on all-cause mortality, cardiovascular mortality and respiratory mortality in seven major South Korean cities over a period spanning 2006–2013. We did time-series analysis using generalized linear models and adjusted for temporal trend, day of the week, holiday, influenza epidemic, and weather. Single lag models and distributed lag models were extensively compared, specifically in terms of lag interval, and adjustment for temporal trend. We also conducted a time-stratified case-crossover analysis. Multivariate meta-regressions with city characteristic variables were conducted in order to assess spatial variation in the lag structure. When considering up to previous 45 days of exposure, we found longer lag associations between PM10 and mortality, particularly in all-cause mortality and respiratory mortality. SO2, the ratio of SO2 to PM10 and gross regional domestic product were all found to positively contribute towards the associations between PM10 and all-cause mortality and cardiovascular mortality. Ulsan (Korea's largest industrial city) was found to have the strongest cumulative percentage increases in all-cause mortality and cardiovascular mortality per 10 μg/m 3 increase of PM10 : 4.9% (95% CI: 2.5, 7.3) and 4.3% (95% CI: −0.9, 9.7) respectively. Busan (Korea's largest seaport city) was found to have the highest cumulative percentage increase in respiratory mortality with an 8.2% increase (95% CI: 2.8, 13.8). In summary, the short-term effects of PM10 on mortality may persist over a period of not just few weeks but longer than a month, and may differ according to regional economy. This study provides public health implication that, in order to minimize the health effects of PM, air quality interventions should focus on not only particulate pollution but also gaseous pollution, such as SO2 . Highlights: We found the lag effects of PM10 on mortality up to 45 days of exposure The effect on cardiovascular mortality was immediate The effect on respiratory mortality persisted over 45 days Cities with higher SO2 level and GRDP per capita had greater PM10 risk